2012
DOI: 10.4028/www.scientific.net/kem.510-511.348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sintering Temperature on Nanostructured Multiferroic BiFeO<sub>3</sub> Ceramics

Abstract: Nanostructured multiferroic BiFeO3(BFO) powders were synthesized by using the co-precipitation method. Calcination of acquired powder was carried out at 400°C for 3h. Uniaxially pressed pellets were sintered at 500°C, 600°C, 700°C and 800°C for 2 hours in air. These samples were characterized for structural, thermal, electrical and magnetic properties. X-ray diffraction (XRD) confirmed the amorphous nature of the as driven powder and phase purity of the calcined BFO sample. The crystallite size varied with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…and Fe 3? ) cause a high leakage current in the material that degrades its ferroelectric properties [10][11][12]. On the other hand, the localized ferromagnetism produced by the canting of spins in BiFeO 3 vanishes at macroscopic level due to the spiral spin structure [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…and Fe 3? ) cause a high leakage current in the material that degrades its ferroelectric properties [10][11][12]. On the other hand, the localized ferromagnetism produced by the canting of spins in BiFeO 3 vanishes at macroscopic level due to the spiral spin structure [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…The disadvantages of these materials are that they possess weak ferroelectric (polarization) and ferromagnetic order parameters. Large number of oxygen vacancies produced due to highly volatile nature of Bi and the multiple oxidation states of Fe (Fe 2+ and Fe 3+ ) cause a high leakage current in the material that degrades its ferroelectric properties [9][10][11] . In order to (i) enhance ferroelectric (polarization) and ferromagnetic order parameters and (ii) reduce leakage current several attempts have been made to replace A and B site of pure BiFeO 3 3 powders were found that bulk densities increased up to 93% of theoretical density and dielectric properties also improved by the Pb-doping as compare to pure BiFeO 3 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric loss is the largest when the sintering temperature is 950 °C. On the one hand, grain boundary, the defect will cause the change of dielectric loss value [29]. On the other hand, the irregular grain size will lead to the abnormal interaction between grains and grain boundaries, which will lead to the increase of friction caused by the domain wall motion and thus, leading to the increase of dielectric loss.…”
Section: Resultsmentioning
confidence: 99%